Submerged cultural heritage and ethnicity in northern Norway: visualizing Sami waterscapes from an archaeological perspective. - Wickler, Stephen (2010)
Changing conceptions of ethnicity within archaeology have had a considerable influence on attitudes towards the Sami and reveal pitfalls associated with the (mis)use of ethnic labels for material culture. This article highlights the importance of Sami water use and waterscapes from a long-term perspective by examining sources pertaining to both saltwater and freshwater within the multicultural context of northern Norway. Possibilities for the documentation of Sami waterscapes are explored with a focus on the challenges facing cultural heritage management. The assertion that Sami waterscapes have been neglected both within and beyond archaeology is illustrated through selected themes. These include the popular Norwegian concept of kystkultur (coastal culture) focusing on Norwegian identity in which the coastal Sami are marginalized or invisible. Another problematic area is ship preservation (fartøyvern) which excludes a majority of Sami watercraft by focusing on larger decked vessels. The general lack of interest in logboats and other ‘primitive’ watercraft within Norwegian archaeology has also had a negative impact on research into Sami boats, especially in the interior. The final section of the article looks at the need to develop a Sami maritime perspective and improve documentation of Sami use of inland waterways.